Development of Mangrove Ecotourism on the Economic Aspects of Coastal Communities in the Arar Islands, Sorong Regency - Sepriyanto Paberu Balik; Sulaiman Kinder; Puput Silfia Adi Saputra; Muhammad Taufik; Munzir Munzir (Proceedings Series on Social Sciences & Humanities, 2024)
Background: The development of coastal communities has benefits that can improve community welfare in the economic aspect. Coastal communities need special attention, especially regarding sustainable programs so that they can be felt for future generations. In particular, the people of the Arar Islands, Sorong Regency, have potential that needs to be developed in order to fulfill the welfare of the community and maintain the stability of the welfare of the local community. The phenomenon that occurs is that using natural resources that are managed sustainably will have a positive economic growth impact on the people of Arar Island. Method: This research uses a qualitative approach, a type of research whose findings are not obtained by statistical procedures or other forms of calculation. A qualitative approach was chosen because it can be used to uncover and understand something behind unknown phenomena. Results: Based on the results of qualitative analysis, it shows that coastal communities in the Arar Islands, Sorong Regency, are mostly categorized as having moderate economic conditions. Thus, the development of this area does not have an impact on changes in the local community's economy. Conclusion: Management of the Mangrove Tourism Area in the Arar Islands, Sorong Regency does not show a positive impact on the economic conditions of the community. This is because the management carried out so far has not been optimal and is temporal in nature and has not been fully supported by the Regency government.